Web-Based Goods Delivery Data Archiving Information System (Case Study of Indah Kartasura Logistics Cargo): Sistem Informasi Pengarsipan Data Pengiriman Barang Berbasis Web (Studi Kasus Indah Logistik Cargo Kartasura) - Murti, Ardila; Naafian, Nuur Rochman; Pantjarani, Ari (Politeknik Harapan Bangsa Surakarta, 2023)
Documents or data are very important and crucial information for a company. One of the important documents for a company is transaction data for a company engaged in a particular field. There needs to be a good filing system so that transaction data can be recorded and used if needed in the future. Indah Logistics Cargo is an agency engaged in the field of freight transportation services to all Regencies and Provinces in Indonesia. The agency already has software that is useful for printing transaction receipts, but there are problems in the customer service section when complaints from customers arise. This happened because there was no data in the software in the customer service section and had to check manually with the administration section. The menual process occurs because there are no access rights granted to the customer service department to view transaction data. The system causes the process to be slow and the customer to be uncomfortable. The purpose of this research is to create a web-based shipping data archiving information system. The author uses the SDLC (System Development Life Cycle) method in the system development process and the PHP programming language and uses the MySQL database. The system that the author designed can produce software that can help the customer service department of CV. Indah Cargo Kartasura in terms of archiving goods delivery transaction data so that the service process to customers is fast and provides a sense of comfort.